2011
DOI: 10.1186/1471-2261-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of retinal emboli during diagnostic and therapeutic cardiac catheterization in patients with coronary artery disease

Abstract: BackgroundCardiac catheterization may cause retinal embolization, a risk factor for cerebrovascular emboli and stroke. We describe the incidence of clinically silent and apparent retinal emboli following diagnostic and interventional coronary catheterization and associated risk factors.MethodsThree hundred selected patients attending a tertiary referral center for diagnostic and therapeutic cardiac catheterization were studied. Retinal examination and examination of the visual field and acuity were done before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…In another comprehensive, prospective study by Kojuri et al in 2011 looking at retinal and visual changes after diagnostic and therapeutic cardiac catheterisation procedures in 300 patients, 6.3% (n=19) of patients were found to have retinal emboli 17 to 96 hours following cardiac catheterisation. 5 This study included patients with diabetes which accounted for one third of their study population but only used the direct ophthalmoscope examination and unfortunately did not report on the breakdown of the exact subtypes of retinal lesions that were diagnosed as embolic in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another comprehensive, prospective study by Kojuri et al in 2011 looking at retinal and visual changes after diagnostic and therapeutic cardiac catheterisation procedures in 300 patients, 6.3% (n=19) of patients were found to have retinal emboli 17 to 96 hours following cardiac catheterisation. 5 This study included patients with diabetes which accounted for one third of their study population but only used the direct ophthalmoscope examination and unfortunately did not report on the breakdown of the exact subtypes of retinal lesions that were diagnosed as embolic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the risk of retinal embolisation to be as high as 55% to 100% after coronary bypass surgery, 1 2 about 1.25% to 13.2% after carotid stenting 3 4 and about 6.3% after cardiac catheterisation. 5 For patients with severe symptomatic aortic stenosis (AS), valvular replacement has been increasingly performed via a femoral catheter technique called transcatheter aortic valve implantation (TAVI). 6 7 While it is a significantly less invasive procedure than traditional surgical valve replacement, current studies suggest that TAVI carries a moderately high cerebrovascular accident rate of up to 5%.…”
Section: Introductionmentioning
confidence: 99%
“…None of them had vision loss. Kojuri et al 8 reported on 300 patients, with 6% having retinal emboli. Only one of the 300 experienced symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of new retinal emboli post-PCI was 6.33 % (19 out of 300 subjects, all asymptomatic) in one landmark study [4]. The same study also found two conventional risk factors (age and hypertension) and operator expertise were strongly associated with new retinal emboli.…”
Section: Discussionmentioning
confidence: 97%